Pengaplikasian Teori Permintaan Pada Konsumsi Rumah Tangga Konsumen Toko Eceran Modern - Indri Maheswari; Prayudha Ananta (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2026)
This study aims to examine the factors influencing consumer behavior in modern retail in Bandar Lampung City. The increase in the number of households in Bandar Lampung has driven the growth of consumption activities, particularly in the modern retail sector. Chandra Super Store Karang, as one of the retail stores with a high level of customer visits, reflects the dynamics of household consumption behavior in the region. From the perspective of demand theory, consumption decisions are influenced by economic factors such as price and income, as well as non-price factors related to consumer preferences, including store atmosphere, comfort, facilities, merchandise, employee interaction, and service quality. This research employs a quantitative inferential approach, which aims to test hypotheses and draw general conclusions from sample data to the broader population. The population consists of households that have shopped at Chandra Super Store Karang, with a sample of 340 respondents selected using purposive sampling. The data used are primary data collected through structured questionnaires, supported by relevant secondary data. Data analysis was conducted using Structural Equation Modeling–Partial Least Squares (SEM-PLS) to assess the validity and reliability of the instruments and to analyze the causal relationships among variables in the research model. The inferential approach was applied to determine the significance of the influence of each independent variable on the dependent variable. The results indicate that promotion and price, store atmosphere, employee interaction, and service quality have a positive and significant effect on household consumption. In addition, household consumption patterns remain focused on fulfilling basic needs as an essential component of daily welfare. This study confirms that the shopping experience plays a strategic role in encouraging consumption and fostering customer loyalty in modern retail stores